FIRST RECORD OF AMBROSIA BEETLE (Euplatypus paralellus Fabricius) INFESTATION ON SONOKEMBANG (Pterocarpus indicus Willd.) FROM MALANG INDONESIA - Tarno, Hagus; Suprapto, Hasan; Himawan, Toto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2014)
Sonokembang (Pterocarpus indicus Willd.) is native of Asia trees, and commonly planted in large numbers as shade trees along roads in Malang. Research was conducted on 76 roads to identify damage intensity of dying trees on sonokembang and clarify the causal agent of dying trees in Malang from May to December 2012. Seven variables was also investigated such as characteristic of tree`s damage, distribution of holes based on sunlight exposure, vertical position of stem, and stem diameter, morphological characteristic of beetle, the intensity of dying trees, and distribution of dying trees. Results showed that there were unique damaging characteristic such as dying and then fallen leaves, holes on the stem and branches, and frass production. Euplatypus parallelus Fabricius was identified as a causal agent of dying sonokembang. There were some indications shown such as beetles preferred to attack stem side with much sunlight exposure, upper stem and medium or bigger size of stem diameter. From 3,206 trees on 76 roads, 69.7% were found dying trees. In dry and rainy season, the intensity of dying trees increased from 8.14 to 9.76% and from 10.26 to 10.79%, respectively. Keywords: Euplatypus paralellus, frass, dying trees, number of holes, sonokembang